Effect of free DNA of environment surface water on bacterial biofilm formation - Saha, Ajora; Sen, Riti; Habib, Suhanin Binte (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology, 2023.